Reversibility of interleukin-1 beta-induced islet destruction and dysfunction by the inhibition of nitric oxide synthase. - Corbett, J A (1994)
We have examined the reversibility of NO-mediated islet dysfunction and destruction induced by interleukin-1 beta (IL-1 beta). Previous studies have shown that pretreatment of islets for 18 h with IL-1 beta results in an inhibition of glucose-stimulated insulin secretion that requires 4 days incubation in the absence of IL-1 beta to restore islet secretory function. In this study we use a sequential experimental design in which islets are first exposed to IL-1 beta for 18 h, and then treated with the NO synthase inhibitor NG-monomethyl-L-arginine (NMMA). Insulin secretion is inhibited by 98% after the 18 h incubation with IL-1 beta, and this inhibition is reversed in a time-dependent fashion by NMMA, with complete recovery of insulin secretion observed 8 h after the inhibition of NO synthase. Inhibition of NO synthase also restores IL-1 beta-induced inhibition of mitochondrial aconitase activity in a time-dependent fashion that mimics the recovery of glucose-stimulated insulin secretion by islets. Ferrous iron and the reducing agents cysteine and thiosulphate accelerate the rate of recovery of insulin secretion, and ferrous iron and thiosulphate stimulate the recovery of islet aconitase activity, suggesting that iron-sulphurcentre reconstitution may be involved in the recovery process. The recovery process also appears to require mRNA transcription, because the transcriptional inhibitor actinomycin D prevents the recovery of insulin secretion by islets after the inhibition of NO synthase. Although IL-1 beta induces the co-expression of NO synthase and cyclo-oxygenase by islets, cyclo-oxygenase is not involved in the recovery of glucose-stimulated insulin secretion. Inhibition of NO synthase also prevents IL-1 beta-induced islet destruction, which otherwise occurs during a 96 h continuous exposure to this cytokine. The destructive effects of IL-1 beta on islet viability are prevented if NMMA is added to islet cultures during the first 24 h of exposure to IL-1 beta, but islet destruction is not prevented if NMMA is added after the first 48 h exposure to IL-1 beta. These results show that IL-1 beta-induced islet dysfunction is reversed by the inhibition of NO synthase, that recovery of insulin secretion is stimulated by iron and reducing agents, and that the recovery process appears to require mRNA transcription. We also show that it is possible to rescue islets from the destructive effects of IL-1 beta if NO synthase is inhibited early after its induction.